Analysis of Impact of Microfinance Services on Business Performance of Small Scale Women Entrepreneurs in Enugu State, Nigeria - Ike , P. C. (Asian Journal of Agriculture and Rural Development, 2013)
This study analyzed access to microfinance services and its impact on performance of small scale women business entrepreneurs in Enugu State, Nigeria between January and December 2012. 71 beneficiaries and 50 non beneficiaries of microfinance services operating different business enterprises were randomly selected from nine local government areas in the State. Data were collected through the use of structured questionnaire and analyzed by the use of descriptive statistical tools such as means and percentages. The Double-Difference (DD) Estimator is used to estimate changes in income from before to after benefiting from services between microfinance beneficiaries and non beneficiaries. Results show that the respondents were aged 37.4 years on the average while over 66% of them were married and about 95% had one form of formal education or the other. All the microfinance service beneficiaries accessed credit and deposit services while none received insurance services. The average income of beneficiaries and non beneficiaries before the study (baseline) were N162,480.00 and N163,572.00 respectively. The income of beneficiaries grew by about 46.67% (from N162,480.00 to N238,480.42 as against that of non beneficiaries which grew by only 11.6% from N163,572.00 to N182,546.35. There was a significant difference between the growth in incomes of the two groups at the 0.05 level. It is recommended that training as one of the core services of microfinance institutions should be vigorously implemented so as to improve the performance of the client entrepreneurs.